The general budget and its objectives from an Islamic perspective: A comparative analytical study with secular systems. - شريف, باقي كريم; الكريم, ياسين صالح عبد; علي, خالد حيدر (Sulaimani Journal for Humanities, 2019)
This research is titled “The public budget and its goals from the perspective of Islam.” Analyzing public budget from the perspective of Islam because public budget, regardless of its names and the stage it went through, is one of the main and effective tools in governing the human entities from the families and tribes to governments and states. But with the development of concept of public budget and its goals in this century, it became the major element of governing system and statehood in a way that reflects the moral and physical power of state. The public budget in Islamic financial and economic system has a great role in protecting public funds in terms of collecting and spending. It plays an effective and main role in protecting physical and moral rights of individuals, groups, institutions and government bodies, it also in fulfilling those rights practically without injustice, corruption and perversion The research tried to shed a light on the public budget, its importance and goals from the perspective of Islam as an existing and effective element in governing states and its entities, it also as a suitable tool to fulfill justice and equality in terms of distribution of fortune and money. He also showed the role of public budget as a correct and suitable plan to achieve comprehensive development in the social, financial, economic, political and security fields.